Examining the Women Issues and Child Abuse as Mirrored by Arundhati Roy’s The God of Small Things - Danish Suleman; Abdul Halim Mohamed (Universitas Muhammadiyah Sidoarjo, 2019)
According to many reports, abuse of women and child is the biggest human rights violation in India. In this qualitative research paper, we are going to examine the causes that lead to women issues and child abuse in India from the perspective of Arundhati Roy’s novel The God of Small Things. In present India, even after its Independence, gender-discrimination and child abuse in Indian society are at worst. In order to understand the causes and reason that creates challenges for women and danger for children in Indian society, we will study the views and experiences of Arundhati Roy as she presented in her selected novel. we will be using a qualitative research methodology to analyze and collect the relevant data using the textual analysis method. For this minor research, we will read and analyze the novel written by Arundhati Roy namely, The God of Small Things (1997). At the end of this study, we will reveal the position of these issues and causes for the women’s issues and child abuse issues. The significance of this study is to create an awareness among the readers on the importance of rights and freedom of women and children in India. This paper depicts how Indian women, as well as children, are facing problems and violence in their daily lives and how we used literature (novel) education to raise and build their personalities in order to contribute fruitfully in Indian society.